The The Effect of Chemistry Teaching Materials on Scientific Literacy and Critical Reasoning in SMA Negeri Langsa - Prasetya, Cyndi; Maisarah (IJCER (International Journal of Chemistry Education Research), 2024)
Scientific literacy is the ability to understand the concepts and processes of science and to use science to solve problems of everyday life. The 21st century demands education to facilitate science literacy in students. However, early observations at SMA Negeri Langsa found that the literacy of students in science was still low, as well as critical. The school has provided complete facilities and has additional textbooks in addition to Chemistry. However, the chemistry materials used are still based on theory. So, this research was carried out to analyze the influence of chemistry teaching materials on science literacy and criticism of students. The method used was design with one-group type pretest-post-test, so there was only one group of samples in this study, the students of the 12th grade MIA-2 consisting of 32 people. The data collection techniques used are tests and observation sheets. Data analysis in this study is descriptive statistics and inferential statistics. The results show that (1) Chemistry teaching materials significantly influence scientific literacy with a percentage of influence of 89.90% and (2) Chemistry teachings also affect critical reasoning significantly with an influence rate of 87.90%. The chemistry learning materials used in this study are LKPD (Learners’ Worksheet) designed using liveworksheet. Thus, the study recommends that teachers and other researchers use chemistries that support scientific literacy and are critical, such as worksheet.